Analysis and Study Indicators for Quarter Car Model with Two Air Suspension System - Mahmood, Mahmood S.; Nassar, Ameen A.; Mohammad, Haider M. (Basrah Journal for Engineering Sciences, 2022)
Modeling and simulation of non-linear quarter-car suspension system for two air spring models (traditional and dynamic new air spring) are contrasted in terms of (RMS) sprung mass acceleration, dynamic load coefficient, the vertical displacement, they are compared. Two and three (DOF) of the mathematical quarter models are implemented in MATLAB/Simulink platform. The Ride Comfort (RC), Dynamic Load Coefficient (DLC) and Road Handling (RH) responses are evaluated as objective functions respectively considering a vehicle speed at 72 km/h and road ISO Class B. The obtained results indicate that the vertical displacement, the (RMS) of the sprung mass acceleration, and dynamic load coefficient values with the new air model system decrease by 10.7 %, 30.6 %, and 13.49 % respectively, in comparison to a tradition suspension system, this one gives more comfort and effortless handling.